Telling Stories, Saving Lives: Creating Narrative Health Messages - Frank, Lauren B. (Health Commun, 2015)
Increasingly, health communication practitioners are exploring the use of narrative storytelling to convey health information. For this study, a narrative film was produced to provide information about the Human Papillomavirus (HPV) and cervical cancer prevention. The storyline centered on Lupita, a young woman recently diagnosed with HPV who informs her family about HPV and the availability of the HPV vaccine for her younger sister. The objective was to examine the roles of identification with characters and narrative involvement (made up of three dimensions: involvement, perceived relevance, and immersion) on perceived response efficacy, perceived severity, and perceived susceptibility to HPV and behavior (discussing the HPV vaccine with a health care provider). A random sample of 450 European American, Mexican American, and African American women between the ages of 25 to 45 living in the Los Angeles area was surveyed by phone before, two weeks after, and six months after viewing the film. The more relevant women found the narrative to their own lives at two weeks, the higher they perceived the severity of the virus and the perceived response efficacy of the vaccine. Also at two weeks, identifying with characters was positively associated with perceived susceptibility to HPV but negatively associated with perceived severity. At six months, identification with specific characters was significantly associated with perceived threat and behavior. These findings suggest that different aspects of narrative health messages should be manipulated depending on the specific beliefs and behaviors being targeted. Implications for narrative message design are discussed.